2011
DOI: 10.1016/j.jalgebra.2011.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Frobenius–Schur indicators in Tambara–Yamagami categories

Abstract: We introduce formulae of Frobenius-Schur indicators of simple objects of Tambara-Yamagami categories. By using techniques of the Fourier transform on finite abelian groups, we study some arithmetic properties of indicators. We also give some applications to Hopf algebras.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…If C is the category of representations of a semisimple Hopf algebra, then C has a canonical pivotal structure and ν n,1 (V ) agrees with Linchenko and Montgomery's. This generalization has some interesting applications to semisimple Hopf algebras, fusion categories and conformal field theories; see [22,25,29,31].…”
Section: Introductionmentioning
confidence: 99%
“…If C is the category of representations of a semisimple Hopf algebra, then C has a canonical pivotal structure and ν n,1 (V ) agrees with Linchenko and Montgomery's. This generalization has some interesting applications to semisimple Hopf algebras, fusion categories and conformal field theories; see [22,25,29,31].…”
Section: Introductionmentioning
confidence: 99%
“…We note that this expression is essentially the same as the formula for the n th higher Frobenius-Schur indicator of a, which has been derived in the mathematical community by very different methods 42,60 .…”
Section: Discussionmentioning
confidence: 75%
“…However, to get a factor planar algebra, we need that m is symmetrically self-dual, i.e., m has Frobenius-Schur indicator 1 [NS07]. The Frobenius-Schur indicators for Tambara-Yamagami categories were completely worked out in [Shi11], where it was shown that ν 2 (a) = δ a 2 ,e and ν 2 (m) = ±, the sign in T Y(A, χ, ±). Hence we must have ± = + to get a factor planar algebra.…”
Section: Examplesmentioning
confidence: 99%